1996
DOI: 10.1080/0968776960040106
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of a mathematics course to CAL: a case study of a large-scale rapid change of resources and organization

Abstract: During 1994-95, first-year maths for the BTechEd degree at the University of Glasgow was studentcentred, teacher-supported A modular online maths course replaced a traditional, lecture-based course. Students worked at their own pace, with timetabled and open access computer classes and/or paper handbooks. The course was evaluated by open-ended measures, and study of examination outcomes, providing us with some pedagogical questions and some recommendations for change. With some adaptation, and with important q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2001
2001
2002
2002

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Simulations are a powerful form of CAL as they have the potential to enable the user to carry out experiments that would otherwise be impossible. Many studies have shown that simulations are equally successful or more effective than real experiments in increasing understanding and promoting interactive learning in subjects ranging from Geography to Medicine (Carstensen, 1993;Cavender and Rutter, 1997;Coleman, 1994;Dewhurst, 1994;Dobson, 1995;Doran and Klein, 1996;Fouad and Burleson, 1997;Guzdial, 1994;Hillis, 1994;Lilienfield and Broering, 1994;Miller and Cooper, 1995;Pamula, 1994;Pollock, McAteer et al, 1996;Samsel, 1994;Sewell, 1996;Silva, 1994;Tosunoglu, Butcher et al, 1996;Woodrow, 1995;Worthington, 1996). However, previous studies have not analysed the factors that affect these learning gains.…”
Section: Introductionmentioning
confidence: 99%
“…Simulations are a powerful form of CAL as they have the potential to enable the user to carry out experiments that would otherwise be impossible. Many studies have shown that simulations are equally successful or more effective than real experiments in increasing understanding and promoting interactive learning in subjects ranging from Geography to Medicine (Carstensen, 1993;Cavender and Rutter, 1997;Coleman, 1994;Dewhurst, 1994;Dobson, 1995;Doran and Klein, 1996;Fouad and Burleson, 1997;Guzdial, 1994;Hillis, 1994;Lilienfield and Broering, 1994;Miller and Cooper, 1995;Pamula, 1994;Pollock, McAteer et al, 1996;Samsel, 1994;Sewell, 1996;Silva, 1994;Tosunoglu, Butcher et al, 1996;Woodrow, 1995;Worthington, 1996). However, previous studies have not analysed the factors that affect these learning gains.…”
Section: Introductionmentioning
confidence: 99%